Strategi Pengembangan Kawasan Pariwisata Sungai Kasie Kota Lubuklinggau - Sofa Nuryati; Hala Haidir; Endy Agustian (Jurnal Ilmiah Wahana Pendidikan, 2023)
In Indonesia the tourism sector has very good potential which is one of the sectors that refers to the economy in Indonesia. Kasie River is a new tourist destination in Lubuk Linggau City with the need for tourism, recreation and entertainment, it will add to the community's economy and increase Human Resources in the Lubuk Linggau region. The purpose of this research is to get a potential to increase the potential that is developed because it has economic and social values ​​for the community around the tourism area that will be developed. The research method used in this study is the quantitative method. Where the population in this study are tourists and residents around the Kasie River area. For the sampling technique in this study, namely purposive sampling, where in data analysis using the SWOT analysis method. So that the results of the research analysis conducted by researchers can be concluded that the Kasie River tourist area has the potential to be developed by having beautiful natural scenic characteristics, this area also has large land and a strategic location so that it can be developed more broadly. There is also a Rafting ride, thereby increasing the attractiveness of the public to visit these tourist attractions. River area development strategy by increasing human resources, creating jobs and becoming a source of income for the surrounding community, increasing promotion and opportunities for collaboration with the private sector and the community.